Malabsorption syndrome aggravates calcium homeostasis impairment in chronic kidney disease patients - Zub, L.; Shkarutyak, A.; Buzdugan, I.; Vivsyannik, V. (Ukrainian Journal of Nephrology and Dialysis, 2022)
Abstract. Recent data on the role of digestive pathology in the progression of chronic kidney disease (CKD) remain scarce. Calcium homeostasis plays an important role in the progression of renal pathology, especially in patients with malabsorption syndrome (MAS). The research aimed to evaluate calcium homeostasis in CKD patients with MAS. Methods. In this cross-sectional observational study, 99 CKD patients with MAS were enrolled. The patients were divided into 4 groups according to the CKD stage and the presence of MAS. Group I included 25 patients with CKD stages 1 and 2 without MAS; Group II consisted of 26 patients with CKD stages 1 and 2, and MAS; Group ІІІ (n = 23) and Group ІV (n = 25) included patients with CKD stage 3 without and with MAS, respectively. According to the morphological study of in vivo biopsies of the small intestinal mucosa, mild and moderate morphological changes were observed among all patients. The levels of calcium, phosphorus, parathyroid hormone, osteocalcin, and calcitonin in the blood, as well as urinary calcium levels, were detected. Results. Pathological changes in calcium metabolism were observed among CKD patients with MAS. The severity of calcium homeostasis disorders was more evident among patients with CKD stage 3 compared with stages 1 and 2. Urinary calcium levels were reduced in the patients of Groups III and IV. No changes were detected in phosphorus levels. Changes in parathyroid hormone and osteocalcin are caused primarily by combined renal pathology with impaired renal calcium absorption. Conclusion. MAS in CKD patients leads to deep violations of calcium homeostasis resulting in rapid CKD progression and bone tissue violation.